Propagação vegetativa de Lecythis spp. por estaquia e miniestaquia - Sant'Ana, Bruna Tomaz (2017)
The sapucaia and sapucaia-mirim are native Brazilian species, which have low occurrence in the forests, due to deforestation to use their timber, and for serving as a source of animal feed, in addition to the rapid loss of viability of their seeds, which hampers sexual propagation. Therefore, vegetative propagation is an option to produce seedlings of these species, by the possibility of using parts of the plant, as material for the production of seedlings. Thus, the aim of this work was to analyze the technique of cutting, minicutting and reinvigoration, to promote rooting, with application of different concentrations of IBA. Experiment I: Lecythis pisonis seedlings at two years old were used and three types of cuttings (apical, intermediate and branches) were made, with an approximate size of 8 cm and with a pair of leaves reduced by half, arranged in a factorial scheme 3 X 4 (three types of cuttings and four concentrations of IBA), with four replicates and 10 cuttings per plot. Experiment II: Propagative material was removed from mature trees at the age of six years. Experiment III: Two-year seedlings underwent a process of reinvigoration by pruning the apex, and after 32 days, the shoots were collected and staked. The experimental design adopted for experiments II and III was completely randomized with four treatments, consisting of four replicates with 10 stakes each. For Experiments I, II and III, the bases of the cuttings were immersed in the concentrations of 0, 1500, 3000 and 6000 mg L-1 of IBA and staked in 55 cm3 filled with expanded vermiculite. Experiment IV: Formation of clonal minijardim, from seedlings propagated by Lecythis lanceolata seeds. The minicuttings had their bases immersed in IBA solutions (0, 2000, 4000 and 8000 mg L-1 ) for ten seconds, and were staked in 55 cm3 tubes with expanded vermiculite. It was used factorial scheme 2 x 4 (two collection periods and four IBA concentrations) was used, with four replicates and 10 minicuttings per plot. At 75 days, cuttings and minicuts were evaluated for survival, presence of calluses and rooting. The results showed that the IBA concentrations did not involve rooting in the cutting process of the two - year - old seedlings and the trees of Lecythis pisonis. In a state of transition through the technique of reinvigoration and the application of 1500 mg L-1 of AIB to the species Lechthis pisonis occurred adventitious rooting of cuttings. Lecythis lanceolata minicut rooting is favored without the use of indolebutyric acid and the minicutting technique indicates the viability of the system for the continuous production of propagules, aiming the production of seedlings.